PENINGKATAN KEMAMPUAN KONSEP BILANGAN 1-20 MELALUI PERMAINAN KONSTRUKTIF PADA ANAK KELOMPOK B TK ABA TANJUNG RAJA - Oktariana Corissa; syafdaningsih syafar; Rukiyah Rukiyah (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2017)
A classroom action Research entitled " Improved Ability of Introduction to The Concept of Numbers 1-20 Through Constructive Games In Children Group B TK ABA Tanjung Raja". This study aims to improve the ability of the concept of numbers through constructive game. The study consisted of 2 cycles, each cycle consisting of 3 meetings that implemented constructive game. Each meeting consists of 4 stages there are: planing, acting, observing and reflecting. Technique of collecting data with action test about concept of number. Research subjects were children aged 5-6 years, amounting to 12 people. Based on the results of analysis the research data there was an increase in the pre cycle, cycle I, and cycle II in a row. There were number of children who got the score with minimum criteria developed as expected in the pre cycle of 2 children (17%), in the first cycle of 8 children (66%), and in cycle II were 11 children (92%). This can be seen from the dominant indicator that emerged from the observation of the child can sequence numbers 1-20, shows the symbol number 1-20, count the number of objects. While the less obvious indicator is matching the number with the number of symbol.